Cost-effectiveness of warfarin care bundles and novel oral anticoagulants for stroke prevention in patients with atrial fibrillation in Thailand - Siok Shen Ng (2020)
© 2019 Elsevier Ltd Introduction: Novel oral anticoagulants (NOACs) and warfarin care bundles (e.g. genotyping, patient self-testing or self-management) are alternatives to usual warfarin care for stroke prevention in patients with atrial fibrillation (AF). We aim to evaluate the cost-effectiveness of NOACs and warfarin care bundles in patients with AF in a middle-income country, Thailand. Materials and methods: A Markov model was used to evaluate the economic and treatment outcomes of warfarin care bundles and NOACs compared with usual warfarin care. Cost-effectiveness was assessed from a societal perspective over a lifetime horizon with 3% discount rate in a hypothetical cohort of 65-year-old atrial fibrillation patients. Input parameters were derived from published literature, meta-analysis and local data when available. The outcome measure was incremental cost per quality-adjusted life years (QALY) gained (ICER). Results: Using USD5104 as the threshold of willingness-to-pay per QALY, patient's self-management of warfarin was cost-effective when compared to usual warfarin care, with an ICER of USD1395/QALY from societal perspective. All NOACs were not cost-effective in Thailand, with ICER ranging from USD8678 to USD14,247/QALY. When compared to the next most effective intervention, patient's self-testing and genotype-guided warfarin dosing were dominated. In the cost-effectiveness acceptability curve, patient's self-management had the highest probability of being cost-effective in Thailand, approximately 78%. Results were robust over a range of inputs in sensitivity analyses. Conclusions: In Thailand, NOACs were unlikely to be cost-effective at current prices. Conversely, patient's self-management is a highly cost-effective intervention and may be considered for adoption in developing regions with resource-limited healthcare systems.